EFFECT OF VITAMIN D DEFICIENCY IN AN ANIMAL MODEL OF POLYCYSTIC OVARY SYNDROME - IMPAIRED CORONARY RELAXATION DETECTED, AS A CARDIOVASCULAR RISK FACTOR. (June 2018) - Hadjadj, L.; Horvath, E.M.; Torok, M.; Monori-Kiss, A.; Pal, E.; Novak, A.; Nadassy, G.L.; Varbiro, S.
Abstract : Objective: Polycystic ovarian syndrome (PCOS) one of the most frequent gynecological illnesses fluencing about 8% of fertile women worldwide. Beyond hyperandrogenic state, vitamin D hypovitaminosis occurs in 70–80% of women suffering from PCOS. Our aim was to investigate the combined effect of these hormonal alterations, considering insulin and testosterone induced relaxation of coronary arterioles. Design and method: 46 adolescent (21–28 day-old), 90–110 gram-weighed female Wistar rats were grouped randomly in 4 groups: vitamin D supplemented groups with (n = 12) and without transdermal testosterone treatment (n = 12) and vitamin D deficient groups with (n = 11) and without transdermal testosterone treatment (n = 11). After 8 weeks of treatment, arterioles (in vivo diameter of 100–200 micrometre) from left anterior coronary artery were obtained and examined in physiological circumstances with pressure miography. With videomicroscopic angiometry the inner and outer radii of the arteriole was evaluated. Insulin and testosterone induced relaxation of the arterioles were obtained and statistically analysed. Immunhistology was used to detect insulin and vitamin D receptor density of coronary arterioles. Results: Insulin induced relaxation was only in vitamin D supplemented, testosterone free group preserved. In the other groups insulin induced relaxation was significantly damaged on a dose dependent manner. Testosterone induced relaxation was reduced in testosterone treated groups regardless to vitamin D status. Conclusions: In hyperadrogenic females both insulin resistance and androgen access results impaired relaxation of coronary arterioles.